Aproveitamento de casca de bacaba (Oenocarpus bacaba Mart.) para o desenvolvimento e aceitação de bebida hidroeletrolítica - Baldissera, Luana (2021)
The consumption of sports beverage, called hydroelectrolytic repositories, has shown an expressive growth in recent years. They are classified as food for practitioners of physical activities and a category of beverage specially formulated to meet the needs related to physical exercise and facilitate rehydration. In general, these drinks are processed for commercialization using dyes and synthetic flavorings in order to obtain the natural flavor and acidity of the fruit. The work consisted of using the Amazonian natural resources, in this case the peel of the bacaba fruit (Oenocarpus bacaba Mart.), Rich in anthocyanins and with potential antioxidant activity to obtain hydroelectrolytic beverages. Two beverages were developed containing 0.5 and 1% bacaba peel extract that presented adequate pH levels, total titratable acidity and total soluble solids. Through the analysis of osmolality, it was observed the development of two hydroelectrolytic beverages from the bacaba shell extract, one isotonic and one hypotonic. Both presented phenolic compounds, such as anthocyanins, which besides providing color to the beverage, collaborate in the antioxidant action and can help regulate some oxidative biochemical disorders caused by acute exercises. The sensorial evaluation showed a positive acceptance of the judges in relation to the addition of bacaba peel extract in the formulations of hydroelectrolytic beverages. The formulations showed a natural red color, which is attractive for those who consume this type of beverage, since these consumers are associated with healthy eating habits that seek natural products. Thus, the formulations developed become a good option for sports beverages, as it uses natural raw material that would be discarded, which in addition to serving as a natural dye, can bring health benefits due to the presence of bioactive compounds.